Costos de producción en la elaboración de los derivados del cacao en la asociación de producción agrícola de cacao nacional La Maná (Asoprocanam) Parroquia de Guasaganda, Cantón La Maná Provincia de Cotopaxi, periodo 2022. - Sánchez Enríquez, Yamileth Stefanía (2023)
The present research work entitled PRODUCTION COSTS IN THE ELABORATION OF COCOA DERIVATIVES IN THE ASSOCIATION OF AGRICULTURAL PRODUCTION OF NATIONAL COCOA LA MANÁ (ASOPROCANAM) GUASAGANDA PARISH, LA MANÁ CANTON, IN THE PROVINCE OF COTOPAXI, DURING THE PERIOD 2022, had as general objective to determine the costs generated in the production of cocoa derivatives through a costing system by production orders in the Association of Agricultural Production of National Cocoa La Maná (ASOPROCANAM). For this a type of investigation, it was essential to use a mixed qualitative-quantitative approach supported by a documentary bibliographic research. In addition, as research techniques an interview was applied to the owner and the observation in the company location to determine the processes carried out in the elaboration of cocoa derivatives. The instruments applied were the interview which used a questionnaire, and the cost elements matrix. Among the results, it was possible to identify the productive processes, as well as the cost elements used in the elaboration of the cocoa-derived products, as well as the chocolate bars, the total costs were $238.75, having a total unit cost of $0.24 cents, with an operating profit of 52% and a net profit of 33%, which turns into $0.17 cents for each chocolate bar sold; In reference to chocolates, the total costs were $206.67, having a total unit cost of $0.07 cents, an operating profit of 70%, and a net profit of 45%, which come into $0.11 cents for each chocolate bar sold; while in the production of cocoa-based beverages, the total costs were $115.29, with a total unit cost of $1.15 cents, an operating profit of 49%, which represents $0.35 cents, and a net profit of 31%, which constitutes $0.70 cents for each hydration drink sold. In conclusion, the design of a costing system for production orders in ASOPROCANAM has allowed an effective management of production costs in the elaboration of cocoa derivatives such as chocolate bars, chocolates and moisturizing drinks, so that this system provides a structured approach to assigning costs to each production order.